2019
DOI: 10.1111/wre.12356
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of invasive Tamarix genotypes in South Africa

Abstract: The exotic Tamarix chinensis and T. ramosissima, believed to have been introduced into South Africa in the early 1900s to control erosion on mine dumps, are invading riparian zones and have been proven to hybridise with T. usneoides, which is native to southern Africa. In this study, we document the abundance of invasive Tamarix genotypes in South Africa. Eleven riparian zones from the Northern, Eastern and Western Cape Provinces were surveyed. Three quadrats of 600 m 2 each were selected per site. Plant densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The study was conducted at three riparian sites in the Western Cape Province, South Africa, where Tamarix invasion had been identified as most prevalent [13]. Both Leeu River (S32,76794 and E21,97958), near the town of Leeu Gamka and the Swart River (S33,16627 and E21,97994) near the town of Prince Albert were in the Central Karoo District of Western Cape.…”
Section: Study Sitementioning
confidence: 99%
See 4 more Smart Citations
“…The study was conducted at three riparian sites in the Western Cape Province, South Africa, where Tamarix invasion had been identified as most prevalent [13]. Both Leeu River (S32,76794 and E21,97958), near the town of Leeu Gamka and the Swart River (S33,16627 and E21,97994) near the town of Prince Albert were in the Central Karoo District of Western Cape.…”
Section: Study Sitementioning
confidence: 99%
“…Exotic Tamarix species have been identified as riparian invaders and are well studied in the United States of America (USA) [9]. Several studies conducted in South Africa have identified riparian zones as regions highly invaded by exotic Tamarix species [10][11][12][13]. Invasive alien plants (IAPs) not only change the plant species composition and distribution patterns but they alter litter quantity and quality.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations